Monocyte-to-Lymphocyte Ratio Is Associated With Tuberculosis Disease and Declines With Anti-TB Treatment in HIV-Infected Children. (1st February 2019) - Choudhary, Rewa K; Wall, Kristin M.; Njuguna, Irene; Pavlinac, Patricia B.; LaCourse, Sylvia M.; Otieno, Vincent; Gatimu, John; Stern, Joshua; Maleche-Obimbo, Elizabeth; Wamalwa, Dalton; John-Stewart, Grace; Cranmer, Lisa M.
Abstract : Background: The blood monocyte-to-lymphocyte ratio (MLR) is associated with active tuberculosis (TB) in adults but has not been evaluated as a TB diagnostic biomarker in HIV-infected children in whom respiratory sampling is difficult. Setting: In a cohort of HIV-infected hospitalized Kenyan children initiating antiretroviral therapy, absolute monocyte and lymphocyte counts were determined at enrollment and 4, 12, and 24 weeks thereafter. Methods: Children were classified as confirmed, unconfirmed, or unlikely pulmonary TB. Receiver operating characteristic curves of MLR cutoff values were generated to distinguish children with confirmed TB from those with unconfirmed and unlikely TB. General estimating equations were used to estimate change in the MLR over time by TB status. Results: Of 160 children with median age 23 months, 13 (8.1%) had confirmed TB and 67 (41.9%) had unconfirmed TB. The median MLR among children with confirmed TB {0.407 [interquartile range (IQR) 0.378–0.675]} was higher than the MLR in children with unconfirmed [0.207 (IQR 0.148–0.348), P < 0.01] or unlikely [0.212 (IQR 0.138–0.391), P = 0.01] TB. The MLR above 0.378 identified children with confirmed TB with 77% sensitivity, 78% specificity, 24% positive predictive value, and 97% negative predictive value. After TB treatment, the median MLR declined in children with confirmed TB and levels were similar to children with unlikely TB after 12 weeks. Conclusions: The blood MLR distinguished HIV-infected children with confirmed TB from those with unlikely TB and declined with TB treatment. The MLR may be a useful diagnostic tool for TB in settings where respiratory-based microbiologic confirmation is inaccessible. Abstract : Supplemental Digital Content is Available in the Text.